Genome-Wide Characterization of Endogenous Retroviruses in Bombyx mori Reveals the Relatives and Activity of env Genes - Feng, Min; Wang, Xiong; Ren, Feifei; Zhang, Nan; Zhou, Yaohong; Sun, Jingchen (Frontiers in Microbiology, 2018)
Endogenous retroviruses (ERVs) are retroviral sequences that remain permanently in the host genome, where they play an important role. Some ERVs have been identified in insect and proven to have infectious properties. However, no information is available regarding Bombyx mori ERVs (BmERVs) to date. Here, we systematically identified 256 potential BmERVs in the silkworm genome via a whole-genome approach. BmERVs were relatively evenly distributed across each of the chromosomes and accounted for about 25% of the silkworm genome. All BmERVs were classified as young ERVs, with insertion times estimated to be less than 10 million years. Seven BmERVs possessing the env gene were identified. With the exception of the Orf133 Helicoverpa armigera nuclear polyhedrosis virus (HaSNPV), the env sequences of BmERVs were distantly related to genes encoding F (Fa and Fb) and GP64 proteins from Group I and Group II NPVs. In addition, only the amino acid sequence of the BmERV-21 envelope protein shared a similar putative furin-like cleavage site and fusion peptide with Group II baculoviruses. All of the env genes in the seven BmERVs were verified to exist in the genome and be expressed in the midgut and fat bodies, which suggested that BmERVs might play an important role in the host biology.